Analysis of Coffee Shop Digital Marketing Strategy through Social Media to Increase Product Sales - Achmad, Gusti Noorlitaria; Elizabeth, Elizabeth; Ridwan, Mochamad; Noorfitri, Karin Cetta Putri; Sofiansyah, Agus (LPPPIPublishing, 2024)
This research aims to analyze coffee shop digital marketing strategy through social media to increase product sales. The approach in this investigate may be a quantitative approach. The population in the study was 30 Coffee Shops in Medan City. Samples were taken randomly from as many as 30 Coffee Shops in Medan City. Theory testing in this inquire about path analysis. Theory testing in this inquire about path analysis. The research results show that digital marketing strategy has a significant effect on social media in Coffee Shops in Medan City. Digital marketing strategy has a significant effect on increase product sales in Coffee Shops in Medan City. Social media has a significant effect on increase product sales in Coffee Shops in Medan City. Digital marketing strategy has a significant effect on increase product sales through social media in Coffee Shops in Medan City.